Descompune în factori:
A=(x+1)totul la a 3 - (x+1) totul la a 2 + (x+1) URGEEENNTT
Răspunsuri la întrebare
Răspuns de
3
(x+1)^3 - (x+1)^2 + (x+1) =
= (x+1) [(x+1)^2 - (x+1) + 1] =
= (x+1)(x^2+2x+1-x-1+1) =
= (x+1)(x^2+x+1)
= (x+1) [(x+1)^2 - (x+1) + 1] =
= (x+1)(x^2+2x+1-x-1+1) =
= (x+1)(x^2+x+1)
Răspuns de
3
[tex]\it (x+1)^3-(x+1)^2+(x+1) = (x+1)[(x+1)^2-(x+1) +1] = \\ \\ = (x+1)(x^2+2x+1-x-1+1) =(x+1)(x^2+x+1)[/tex]
Alte întrebări interesante
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Biologie,
9 ani în urmă
Limba română,
9 ani în urmă